2011
DOI: 10.1021/es103917r
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Detailed Survey on Pollution by Multiple Perfluorinated Compounds in the Tokyo Bay Basin of Japan

Abstract: Pollution from 35 perfluorinated compounds (PFCs) in the water of the Tokyo Bay basin was examined. The water in the basin contained relatively high levels of perfluorononanoate (PFNA), perfluorooctanoate (PFOA), and perfluorooctane sulfonate (PFOS) compared to the other PFCs, which were present at concentrations of 20.1 ng/L, 6.7 ng/L, and 5.8 ng/L, respectively. In contrast, the concentrations of their precursors and degradation products were an order of magnitude lower. Sewage treatment plant (STP) effluent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…A previous study suggested that PFNA in Japanese rivers was potentially derived from consumer products made in Japan (Murakami et al, 2008). It was also reported that PFNA was the most predominant compound among PFASs investigated in rivers in the Tokyo Bay basin (Zushi et al, 2011). This coincided with our study and suggests that PFNA was used in large amounts in consumer products and might be a substitute for PFOA in Japan.…”
Section: Concentration and Homologue Profiles In Each Pfas Groupsupporting
confidence: 90%
See 3 more Smart Citations
“…A previous study suggested that PFNA in Japanese rivers was potentially derived from consumer products made in Japan (Murakami et al, 2008). It was also reported that PFNA was the most predominant compound among PFASs investigated in rivers in the Tokyo Bay basin (Zushi et al, 2011). This coincided with our study and suggests that PFNA was used in large amounts in consumer products and might be a substitute for PFOA in Japan.…”
Section: Concentration and Homologue Profiles In Each Pfas Groupsupporting
confidence: 90%
“…The concentrations of detected PFCA precursors ranged from <LOQ-24 ± 14 ng g À1 for 8:2 FTCA and <LOQ-17 ± 13 ng g À1 for 10:2 FTCA (Table S2). In a previous study, FTCAs and FTUCAs were also detected at low concentrations (<0.09 ng g À1 ) in rivers in the Tokyo Bay basin (Zushi et al, 2011). These FTCAs and FTUCAs may be impurities generated during manufacturing, since their concentrations are too low for them to have served as intentional ingredients.…”
Section: Precursors Of Pfcas (Fluorotelomer Carboxylic Acids (Ftcas)mentioning
confidence: 82%
See 2 more Smart Citations
“…[18,31] Modelling studies have also shown that WWTPs are the predominant sources of PFASs in the aquatic environment, [32] although diffuse non-point sources of pollution exist in urban areas. [33] Land application of sewage sludge is another pathway of PFASs to the food chain. Studies have shown that current wastewater treatment processes do not adequately remove PFASs present in the waste stream.…”
Section: Need For Understanding and Controlling Of Sources Of Environmentioning
confidence: 99%